2020
DOI: 10.1016/j.nic.2019.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging in Schizophrenia

Abstract: Psychotic disorders are mental illnesses characterized by difficulties in reality testing 1 . Schizophrenia is a severe and chronic psychotic disorder with a life time prevalence of about 1%. Onset is typically in adolescence or early adulthood; characteristic symptoms include abnormally held beliefs (delusions), altered perceptions (hallucinations), disordered thinking, disorganized behavior (collectively positive symptoms) and deficits in motivation, affect, and socialization (negative symptoms). Diagnosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(46 citation statements)
references
References 90 publications
3
42
0
1
Order By: Relevance
“…Our research is in line with the growing interest in predictive modeling using neuroimaging and machine learning methods (Janssen et al, 2018;Keshavan et al, 2020). Most machine learning studies have focused on differential diagnosis, identifying brain signatures that discriminate patients from healthy controls, and further established objective signs of disease pathology (Lai, 2019).…”
Section: Discussionsupporting
confidence: 61%
“…Our research is in line with the growing interest in predictive modeling using neuroimaging and machine learning methods (Janssen et al, 2018;Keshavan et al, 2020). Most machine learning studies have focused on differential diagnosis, identifying brain signatures that discriminate patients from healthy controls, and further established objective signs of disease pathology (Lai, 2019).…”
Section: Discussionsupporting
confidence: 61%
“…Although they are not yet sufficiently specific to be of diagnostic value, substantive evidence of structural, functional, and neurochemical brain alterations in SZ corroborates both the neurodevelopmental and neurodegenerative models of this disorder. 37 A comprehensive meta-analysis of more than 18,000 people found that those with SZ had lower brain volumes than controls, both globally (total volumes) and in several specific cortical and subcortical structures. Curiously, the findings were similar regardless of antipsychotic use.…”
Section: Neuroimaging Insightsmentioning
confidence: 99%
“…Schizophrenia is a complex disorder characterized by neuroanatomical ( 23 , 24 ), genetic ( 25 , 26 ), psychophysiological ( 27 , 28 ) and functional ( 29 , 30 ) impairments. Among these deficits, cognitive decline is a core feature of the disorder as evidenced by neuropsychological ( 31 , 32 ) as well as functional neuroimaging ( 33 , 34 ) studies.…”
Section: Introductionmentioning
confidence: 99%